ANALYSIS OF THE INTERACTION OF COMPONENTS OF CERAMIC COMPOSITES WITH MODIFIED CARBON NANOSTRUCTURES - Шамсутдинов, Баходир (SWorldJournal, 2024)
The article presents the process of interaction of ceramic matrix components with modified multi-layered carbon nanotubes (CNTs). The processes of functionalization and decoration of nanotubes were considered in order to improve their integration into th